Working Capital: The Power of Labor's Pensions - Quarter, Jack (Relations industrielles / Industrial Relations, 2001)
Working Capital: The Power of Labor's Pensions, edited by Archon Fung, Tessa Hebb, and Joel Rogers, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Pension funds; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social investing